Influence of excess weight on lower-extremity vertical stiffness and metabolic cost of walking. Issue 4 (20th April 2020) - Bode, Victoria G.; Croce, Ronald V.; Quinn, Timothy J.; Laroche, Dain P.
ABSTRACT: The purpose was to test whether lower-extremity vertical stiffness and gait mechanics explain differences in energy cost of walking (Cw) between individuals with normal weight (NW) and obesity (OB). Ten OB (33.1 ± 2.0 kg m −2 ) and 10 NW (24.2 ± 1.3 kg m −2 ) walked for six minutes on an instrumented treadmill at 1.25 m s −1 while Cw, lower-extremity kinematics, and vertical stiffness ( K vert ) were measured. NW completed another trial with a loaded vest (NWL) to simulate the BMI of the obese group. Cw was 24% greater in OB (277.5 ± 45.3 J m −1 ) and 23% greater in NWL (272.7 ± 35.7 J m −1 ) than NW (211.0 ± 27.0 J m −1, P  < 0.005). Mass-specific Cw (Cwkg ) wasn't different between conditions ( P  = 0.085). Lower-extremity K vert was 40% higher in OB (32.7 ± 5.2 kN m −1 ) than NW (23.3 ± 4.7 kN m −1, P  < 0.001), but neither was different from NWL (27.5 ± 3.4 kN m −1, P  > 0.05). Mass-specific K vert ( P  = 0.081) was similar across conditions. K vert was related to Cw ( r  = 0.55, P  = 0.001). Cwkg wasn't different between NW or OB, but there was a negative correlation between BMI and Cwkg driven by lower Cwkg in NWL. Cw and K vert covaried in proportion to body mass, but mass-specific K vert was unrelated to Cwkg . Mass-specific K vert was lower in NWL than OB due to NWL's greater angle of attack, center of mass displacement, and joint range of motion.